2021
DOI: 10.1186/s40494-021-00531-2
|View full text |Cite
|
Sign up to set email alerts
|

Technical features of a ninth-century silver vessel of southern China uncovered from Famen Monastery, Shaanxi province

Abstract: Silver art is an important feature of the Tang dynasty in China and the manufacturing center for silver shifted from north to south after the mid-eighth century CE. The typology, stylistics, and iconography of silver vessels from both regions have been studied in detail. However, their technical characteristics have rarely been discussed, in particular, those of the southern ones. The current study presents a non-invasive scientific analysis on a partially-gilded silver box from Jiangnanxidao of Tang (southern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…There are some studies on the gold and silver inlaying and gilding processes on bronze at home and abroad. Based on the available research, the basic steps of the gilding method used in different regions are approximately the same [14][15][16][17]. A study by Oddy et al on the composition of decoration on gold vessels, silver vessels, and bronze vessels from the ancient and medieval periods found that the statue of the Roman emperor Niello (1st century AD) was made of bronze.…”
Section: Introductionmentioning
confidence: 99%
“…There are some studies on the gold and silver inlaying and gilding processes on bronze at home and abroad. Based on the available research, the basic steps of the gilding method used in different regions are approximately the same [14][15][16][17]. A study by Oddy et al on the composition of decoration on gold vessels, silver vessels, and bronze vessels from the ancient and medieval periods found that the statue of the Roman emperor Niello (1st century AD) was made of bronze.…”
Section: Introductionmentioning
confidence: 99%